Protection Against Solar Ultraviolet Radiation in Outdoor Construction Workers: Study Protocol for a Non-randomized Controlled Intervention Study - Keurentjes, Anne J.; Kezic, Sanja; Rustemeyer, Thomas; Hulshof, Carel T. J.; van der Molen, Henk F. (Frontiers in Public Health, 2021)
Introduction Non-melanoma skin cancer (NMSC) incidence is increasing, and occupational solar exposure contributes greatly to the overall lifetime ultraviolet radiation (UVR) dose. This is reflected in an excess risk of NMSC showing up to threefold increase in outdoor workers. Risk of NMSC can be reduced if appropriate measures to reduce UVR-exposure are taken. Regular use of sunscreens showed reduced risk of NMSC. However, sun-safety behavior in outdoor workers is poor. The objective of this study is to investigate the effectiveness of an intervention aiming at increasing sunscreen use by construction workers. Methods This non-randomized controlled intervention study is comprised of two intervention and control groups recruited at four different construction sites in the Netherlands. The study population comprises approximately 200 construction workers, aged 18 years or older, followed during twelve weeks. The intervention consists of providing dispensers with sunscreens (SPF 50+) at construction sites and regular feedback on the application achieved by continuous electronic monitoring. All groups will receive basic information on UV-exposure and skin protection. Stratum corneum (SC) samples will be collected for measurement of biomarkers to assess internal UV-dose. External UV-dose will be assessed by personal UV-sensors worn by the workers during work-shifts in both groups. To detect presence of actinic keratosis (AK) or NMSC, a skin check of body parts exposed to the sun will be performed at the end of the study. The effect of the intervention will be assessed from data on self-reported sunscreen use by means of questionnaires collected on baseline and after 12 weeks of intervention (primary outcome). Levels of SC biomarkers of internal UV-dose, external UV-dose, number of sunburn episodes, and prevalence of NMSC including AK will be assessed as secondary outcomes. The electronically monitored sunscreen consumption will be assessed as process outcome. Discussion This study is intended to provide evidence of the effectiveness of a technology-driven intervention to increase sunscreen use in outdoor construction workers. Furthermore, it will increase insight in the UV-protective behavior, external and internal UV-exposure, and the prevalence of NMSC, including AK, in construction workers. Trial registration The Netherlands Trial Register (NTR): NL8462 Registered on March 19, 2020.